Mapeamento de tecnologias informacionais sobre dados abertos em saúde pública: destino de repasses financeiros federais - Rodrigues, Fernando de Assis [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The Brazilian public health is hightlighted in the media. The discourse wich covers various social actors, the quality of public health services provided to citizens, raises questions such as the destination of the application of financial transfers from the Federal Government. The construction of mechanisms, via the Information and Communication Technologies, allow to these actors relate the governmental resources with their respective destinations, leads to an expansion of the public on monitoring the State's actions in this sector and so increases the possibilities of citizen participation in the mechanisms of control over the state as the monitoring of activities and processes of government. In this scenario, it is also important to ensure that access to such informations be open to any public and that data on this topic meet the principles of open data, which ensures the building, outside the public administration and their official websites, graphics and views and crossing these data with other information sources. The goal of this study is to identify, on the official sites of the Federal Government, existing technological resources to the process of providing data of government financial transfers destiny intended for public health and proposal of a prototype as a reference for the construction of technological resources for locating sources of data on allocation of financial resources for public health. The established methodology is exploratory analysis of the four official Federal Government sites, found through searches on search engine: the National Treasury Secretariat (Treasure Ministry), the National Health Fund (Health Ministry), the portal transparency of the Federal Government (Union Comptroller General)... (Complete abstract click electronic access below)

A saúde pública brasileira é um tema que está em evidência nos meios de comunicação. A discussão, que abarca diversos atores sociais, da qualidade dos serviços de saúde pública prestados aos cidadãos, levanta questionamentos tais como o destino da aplicação dos repasses de recursos financeiros oriundos do Governo Federal. A construção de mecanismos, via Tecnologias de Informação e Comunicação, que permitam a esses atores relacionar recursos financeiros governamentais com o seus respectivos destinos, leva a ampliação do acompanhamento público sobre as ações do Estado neste setor e aumenta tanto as possibilidades de participação do cidadão nos mecanismos de controle sobre o Estado quanto o acompanhamento das atividades e processos da administração pública. Nesse cenário, também é importante garantir que o acesso a essas informações seja aberto a qualquer público e que os dados sobre este tema atendam os princípios de dado aberto, o que garante a construção, externa a administração pública e seus sítios oficiais, de gráficos e visualizações e o cruzamento destes dados com outras fontes de informação. O objetivo geral deste estudo é identificar, em sítios oficiais do Governo Federal, recursos tecnológicos existentes com a finalidade de tornar acessíveis os dados governamentais sobre o encaminhamento dos repasses financeiros destinados a área da saúde pública e a apresentação de protótipo como elemento de referência para construção de recursos tecnológicos que permitam a localização de fontes de dados sobre destino de recursos financeiros destinados à saúde pública. A metodologia estabelecida é a análise exploratória de quatro sítios oficiais, encontrados através de pesquisas em...
Keywords: Tecnologia da informação; Saúde pública - Finanças - Brasil; Ciência da informação; Information technology; Public health; Information science